2023
DOI: 10.3390/ijms242216529
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic and Transcriptomic Analysis of Phenol Degradation and Tolerance in Acinetobacter lwoffii through Adaptive Evolution

Nan Xu,
Xiaojing Yang,
Qiyuan Yang
et al.

Abstract: Microorganism-based methods have been widely applied for the treatment of phenol-polluted environments. The previously isolated Acinetobacter lwoffii NL1 strain could completely degrade 0.5 g/L phenol within 12 h, but not higher concentrations of phenol. In this study, we developed an evolutionary strain NL115, through adaptive laboratory evolution, which possessed improved degradation ability and was able to degrade 1.5 g/L phenol within 12 h. Compared with that of the starting strain NL1, the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Recent studies by Xu et al [80,81] demonstrated that Acinetobacter iwoffii NL1 degrades phenol via the ortho-cleavage pathway instead of the meta-cleavage pathway. This bacterium's capability to degrade the phenol ortho-pathway and its resistance to heavy metals and antibiotics position it as a promising candidate for wastewater treatment.…”
Section: Microorganisms That Degrade Phenolic Compounds and Bioremedi...mentioning
confidence: 99%
“…Recent studies by Xu et al [80,81] demonstrated that Acinetobacter iwoffii NL1 degrades phenol via the ortho-cleavage pathway instead of the meta-cleavage pathway. This bacterium's capability to degrade the phenol ortho-pathway and its resistance to heavy metals and antibiotics position it as a promising candidate for wastewater treatment.…”
Section: Microorganisms That Degrade Phenolic Compounds and Bioremedi...mentioning
confidence: 99%